Evaluasi Penerapan Constructability pada Proyek Konstruksi Bangunan Gedung - Yunianto, Dony Yunianto; Utomo Dwi Hatmoko, Jati; Hidayat, Arif (Department of Civil Engineering, Diponegoro University, 2014)
Constructability is the integration of expertise for the planning and designing process of a project. Constrcutabilty implementation better starts from planning phase; therefore, this phase has major influence for the whole project. This research is aimed to evaluate the constructability implementation on design bid build project and design and build system. The research method is qualitative and quantitative approach; qualitative approach applied to learn things that influence the construction implementation evaluation, meanwhile, quantitative method is applied to receive analysis from each level of constructability implementation of the project. Researcher evaluates the constructability implementation on the designated building project including the research on constructability implementation phases, projects’s life cycles, and the stakeholder’s roles. The overall average value received from the constructability implementation on Universitas Diponegoro Building project is 2.44, and for the overall average value of private Apartment project is 3.03. The result received from the two designated project is that the private apartment project generated a better value compare to the Universitas Diponegoro Building project. The project life cycles also show that the private apartment building project was able to optimize the execution time by using the constructability and the design also more constructable.